The Moderating Effect of Competency on the Influence of Work Environment and Behavioral Integrity on Work Performance of State Civil Servant Employees at Lubuklinggau Environmental Service - Effendi, M.; Azhar, Rudi; Rabeta, Yulpa (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This research examines the moderating effect of competency on the relationship between work environment and work performance of Lubuklinggau Environmental Service employees who were members of the State Civil Service (ASN). Finding out how much impact employee competence has on the correlation between these two factors and output is the main objective of this research. This research used a quantitative approach by collecting data through questionnaires. Lubuklinggau Environmental Service staff from ASN were used as research samples. To test the research hypothesis, we used moderation analysis and multiple regressions. Employee performance was positively influenced by the work environment and behavioral integrity, according to the research. In contrast, the relationship between workplace integrity, employee performance, and behavioral integrity was influenced by the employee's skill level. Organizational management should pay attention to the work environment, behavioral integrity, and the need to develop employee competency in order to improve the performance of ASN workers. These results were very important in this regard. With luck, this research will increase knowledge about public sector human resource management and provide an idea of ​​how ASN staff can work more efficiently.